Analytics stories : using data to make good things happen - Winston, Wayne L. (Indianapolis, IN : John Wiley & Sons, Inc., 2021)
Inform your own analyses by seeing how one of the best data analysts in the world approaches analytics problems Analytics Stories: How to Make Good Things Happen is a thoughtful, incisive, and entertaining exploration of the application of analytics to real-world problems and situations. Covering fields as diverse as sports, finance, politics, healthcare, and business, Analytics Stories bridges the gap between the oft inscrutable world of data analytics and the concrete problems it solves. Distinguished professor and author Wayne L. Winston answers questions like: Was Liverpool over Barcelona the greatest upset in sports history? Was Derek Jeter a great infielder What's wrong with the NFL QB rating? How did Madoff keep his fund going? Does a mutual fund's past performance predict future performance? What caused the Crash of 2008? Can we predict where crimes are likely to occur? Is the lot of the American worker improving? How can analytics save the US Republic? The birth of evidence-based medicine: How did James Lind know citrus fruits cured scurvy? How can I objectively compare hospitals? How can we predict heart attacks in real time? How does a retail store know if you're pregnant? How can I use A/B testing to improve sales from my website? How can analytics help me write a hit song? Perfect for anyone with the word "analyst" in their job title, Analytics Stories illuminates the process of applying analytic principles to practical problems and highlights the potential pitfalls that await careless analysts.
Part I. What Happened? Preliminaries -- Was the 1969 Draft Lottery Fair? -- Who Won the 2000 Election: Bush or Gore? -- Was Liverpool Over Barcelona the Greatest Upset in Sports History? -- How Did Bernie Madoff Keep His Fund Going? -- Is the Lot of the American Worker Improving? -- Measuring Income Inequality with the Gini, Palm, and Atkinson Indices -- Modeling Relationships Between Two Variables -- Intergenerational Mobility -- Is Anderson Elementary School a Bad School? -- Value-Added Assessments of Teacher Effectiveness -- Berkeley, Buses, Cars, and Planes -- Is Carmelo Anthony a Hall of Famer? -- Was Derek Jeter a great fielder? -- "Drive for show and putt for dough?" -- What's wrong with the NFL QB rating? -- Some sports have all the luck -- Gerrymandering -- Evidence-based medicine -- How do we compare hospitals? -- What is the worst health care problem in my country? -- What will happen? -- Does a mutual fund's past performance predict future performance? -- Is Vegas good a picking NFL games? -- Will my new hires be good employees? -- Should I go to State U or Princeton? -- Will my favorite sports team be great next year? -- How did central bankers fail to predict the 2008 recession? -- How does Target know if you're pregnant? -- How does Netflix recommend movies and TV shows? -- Can we predict heart attacks in real time? -- Is proactive policing effective? -- Guess how many are coming to dinner? -- Can prediction markets predict the future? -- The ABCs of polling -- How did Buzzfeed make the dress go viral? -- Predicting Game of Thrones TV ratings -- Why did it happened? Does smoking cause lung cancer? -- Why are the Houston rockets a good basketball team? -- Why have sacrifice bunts and intentional walks nearly disappeared? -- Do NFL teams pass too much and go for it often enough on fourth down -- What caused the 1854 London cholera outbreak? -- What affects the sales of a retail product? -- Why does the Pareto Principle explain so many things? -- Does where you grow up matter? -- The waiting is the hardest part -- Are roundabouts a good idea? -- Red light, green light, or no light? -- How do I make good things happen? How can we improve K-12 education? -- Can A/B testing improve my website's performance? -- How should I allocate my retirement portfolio? -- How do hedge funds work? -- How much should we order and when should we order? -- How does the UPS driver know the order to deliver packages? -- Can data win a Presidential election? -- Can analytics recognize, predict, or write a hit song? -- Can an algorithm improve parole decisions? -- How do baseball teams decide where to shift fielders? -- Did analytics help the Mavericks win the 2011 NBA title? -- Who gets the house in the Hampton's?
Includes index.
Description based on online resource; title from digital title page (viewed on May 08, 2023).
John Wiley and Sons
Keywords: Big data -- Social aspects; Decision making -- Data processing; x; x; COMPUTERS -- Business & Productivity Software -- Business Intelligence; Big data -- Social aspects; Decision making -- Data processing